EFEKTIVITAS KERJA BALAI PENYULUH PERTANIAN KECAMATAN PINGGIR KABUPATEN BENGKALIS - Ayu Oktabriyanti; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The Work effectiveness of an employee is very important because the success ofand organization is measured with the effectiviness concept. The work effectiveness ofInstructor agriculture establishment on pinggir to achieve goal can’t lose fromendorsement input organization they have. Bassicaly to achieve effectivenessorganization will measuring with five indicators, that is Human resources, Fund,Facilities and Infrastruktur, and Standar Operational Procedure. When all the Indicatorseffectiveness of organization fulfilled accordingly the organization will effectiveness onimplementation assignment.The present research seeks to find out the work effectiveness of instructoragriculture establishment and to know the factors affecting the work effectiveness ofemployees at instructor agriculture etablisment. The informants were selected usingpurposing sampling technique and there are five of them who are competent to knowand understand the rearch problems. The data were collected througt and observation,interview and documents and were analyzed using a descriptive approach. The researchindicator is work program, Division of Assigment, Coordination, and Counseling.The results show that work effectiveness of instructor agriculture establisment isstill ineffective. Therefore, it is suggested that increased work effectiveness of instructoragricultur establishment on Pinggir should be considered.Key words: Work effectiveness, Work effectiveness organization, Instructor agriculture